Influence of inverse spinel structured CuGa2O4 on microwave dielectric properties of normal spinel ZnGa2O4 ceramics. Issue 4 (28th November 2017) - Lu, Xiaochi; Bian, Wenjie; Li, Yaoyao; Zhu, Haikui; Fu, Zhenxiao; Zhang, Qitu
Abstract: Spinel Zn1‐ x Cu x Ga2 O4 ( x  =   0‐0.15) ceramics were prepared by the conventional solid‐state method. Only a single phase was indexed in all samples. The continuous lattice contraction of ZnGa2 O4 unit cell was caused by Cu 2+ substitution, and the lattice parameter shows a linear correlation with the content of Cu. The refined crystal structure parameters suggest that Cu 2+ preferentially occupies the octahedron site, and the degree of inversion of Zn1‐ x Cu x Ga2 O4 ( x  =   0‐0.15) ceramics almost equals to the content of Cu 2+ . The relative intensity of A*1g mode in Raman spectra confirm that the degree of inversion climbed with the growing content of Cu 2+ . The experimental and theoretical dielectric constant of Zn1‐ x Cu x Ga2 O4 ceramics fit well. Zn1‐ x Cu x Ga2 O4 ( x  =   0.01) ceramics sintered at 1400°C for 2 h exhibited good microwave dielectric properties, with ε r  = 9.88, Q  ×  f  =   131, 445 GHz, tan δ = 6.85 × 10 −5, and τ f   = −60 ppm/°C.